Protective Effects of Hydroalcoholic Extract of Ferulago Angulata Against Gentamicin-induced Nephrotoxicity in Rats (Iranian Journal of Kidney Diseases, 2016)
Introduction. Gentamicin can lead to acute tubular injury and kidney dysfunction. This study aimed to evaluate the effect of Ferulago angulata on kidney function and other markers in rats with gentamicin-induced nephrotoxicity. Materials and Methods. Forty-eight male Wistar rats were divided into the following groups: group 1, the controls; group 2, rats receiving gentamicin (120 mg/kg body weight per day, intraperitoneal) for 7 days without treatment; groups 3, 4 and 5, rats receiving gentamicin for 7 days and oral treatment with 200 mg/kg, 400 mg/kg, and 800 mg/kg body weight per day of Ferulago angulate extract, respectively. Measurements included serum levels of creatinine, urea, uric acid, lipids, ferric-reducing antioxidant power, and protein carbonyl; kidney and serum levels of malondialdehyde; and serum and renal levels of tumor necrosis factor-α. Histopathology of kidney tissue was examined as well as renal catalase, superoxide dismutase, and vitamin C. Results. Compared to treatment with gentamicin only, treatment with Ferulago angulata resulted in a significantly higher high-density lipoprotein cholesterol, ferric-reducing antioxidant plasma, renal catalase, superoxide dismutase, and vitamin C levels. It was also associated with significantly lower serum levels of creatinine, urea, uric acid, malondialdehyde, protein carbonyl, tumor necrosis factor-α, total cholesterol, triglyceride, low-density lipoprotein cholesterol, and very low-density lipoprotein cholesterol. Ferulago angulate was linked with a lower renal gene expression of tumor necrosis factor-α. Conclusions. The present study suggests that Ferulago angulate extract has protective effects against nephrotoxicity due to gentamicin.